Efforts to Improve Understanding in Learning the Material on Living in Peace and Forgiving Each Other at SD Negeri 081724 Silau Dunia by Using Scaffolding - Hasanah, Siti; Harahap, Diana Fajar Anggraini; Saidah; Ritonga, Muhammad Ali Sukri; Apriani, Nurhapni; Marlina, Latifah (MANDAILING GLOBAL EDUKASIA, 2024)
Islamic Religious Education learning aims to shape the character of students to have a tolerant, peaceful attitude, and be able to forgive each other in everyday life. However, in practice, students' understanding of the material Living in Peace and Forgiving Each Other still often experiences obstacles, both in terms of concept and its application in social life. This study aims to improve students' understanding by implementing a scaffolding strategy, a learning approach that provides gradual guidance according to students' needs until they are able to understand the concept independently. The research method used is classroom action with stages of planning, implementation, observation, and reflection. The results of the study showed that the application of scaffolding can improve students' understanding of the concept of living in peace and forgiving each other. Students become more active in discussions, understand the material more easily, and are able to relate the concepts learned to everyday life. Thus, the use of scaffolding as a learning strategy can be an effective alternative in improving students' understanding of moral and social values ​​in Islamic Religious Education. The research method used is classroom action with stages of planning, implementation, observation, and reflection. The results of the study showed that the application of scaffolding can improve students' understanding of the concept of living in peace and forgiving each other. Students become more enthusiastic about learning, understand the material more easily, and are able to connect the values ​​they learn with their personal experiences.